Strengthening of the Kneser theorem on zeros of solutions of the equation $u″ + q(t)u = 0$ using one functional equation - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We present conditions under which a linear homogeneous second-order equation is nonoscillatory on a semiaxis and conditions under which its solutions have infinitely many zeros.